Reforming the Global Economic Architecture: Lessons from Recent Crises - Stiglitz, Joseph E. (Journal of Finance, 1999)
Recent turmoil in international financial markets has raised a set of fundamental questions for the global community: Is the set of international financial arrangements, established after the Great Depression and World War II and modified after the abandonment of the gold standard in 1973, up to the challenges of the twenty-first century? Are minor modifications such as slight changes in the governance of the international financial institutions, increased transparency, or surveillance! all that is required to adapt these institutions to the needs of modern economies, or are more fundamental changes necessary? Today, although much has been proposed, discussed, and argued, no consensus on desirable changes has yet been reached. In the meantime, what can countries, especially the poor, the small, and the less developed, do to protect themselves from the seeming ravages of storms brought on by international financial instability?